Using 4x^2 - 9y^2 = 36

Find y by implicit differentiation and then solve the equation explicitly for y and differentiate to get y' in terms of x.

1 answer

I am sure you wanted y'

8x - 18y dy/dx = 0
-18y dy/dx = -8x
dy/dx = 8x/(18y) = 4x/(9y)

-9y^2 = 36 - 4x^2
y^2 = (4x^2 - 36)/9
y = (4x^2 - 36)^(1/2) /3
dy/dx = (1/6) (4x^2 - 36)^(-1/2) (8x)
= (4/3)(x)(4x^2 - 36)^(-1/2)
Similar Questions
  1. I just need the 3rd part!!!(2 points) Let y be defined implicitly by the equation ln(2y)=5xy. Use implicit differentiation to
    1. answers icon 1 answer
  2. If cos(3 x)�6Ó14 x e^2 y=0, find [ dy/dx] using implicit differentiation.In this problem, you should differentiate both sides
    1. answers icon 0 answers
  3. Alright so implicit differentiation is just not working out for me.Use implicit differentiation to find the slope of the tangent
    1. answers icon 1 answer
  4. A. find y' by implicit differentiation.B. solve th equation explicitly for y and differentiate to get y' in terms of x. cos (x)
    1. answers icon 1 answer
more similar questions